ORGANIZATION CRISIS INTERVENTION: INCORPORATING A COUNSELING STRATEGY - Ahmad Rozelan , Yunus; Amir, Aris; Wan Walada Faiqah, Maulud; Adi, Fahrudin (2012)
Crisis Intervention as a domain of research has grown by benefiting from more established disciplines. However, a commonality in the early stages of applying established theories to crisis intervention is the lack of grounded research frameworks. This paper reviews crisis intervention model develops a conceptual framework that illustrates how this construct can serve crisis intervention research. Based on a review of psychological and sociological literature, the paper proposes a model of strategies in counseling to organization crisis intervention. Suggestions for future research and practical implications are also presented.